Guinness world records 2011 : exploding with thousands of new records - Glenday, Craig ([Place of publication not identifed] : [publisher not identified], 2011)
Presents the biggest, smallest, fastest, longest, and other record setters for 2010 in such categories as space, human achievements, sports, entertainment, science, technology, and engineering.
Includes index.
Keywords: CURIOSITIES AND WONDERS